A Framework for Monitoring Relational Quality in B2B Technology Partnerships - Francis Bidault; Manfred Lüth; Olaf Plötner (European School of Management and Technology (ESMT), 2009)
The purpose of this paper is to propose a framework for the monitoring of new technology introduction in a B2B environment. We focus on B2B environments, i.e. on projects where a new technological solution is implemented (and often jointly developed) with a client being either a company or an organization. In such a situation, where a supplier and its client agree to implement a new technology, both are exposed to a risk. The management of these risks can be handled through a couple of approaches: control or trust. The management literature has put a lot of attention on these two modes that play an important role because they drive the quality of the relationship between partners. We will explore their respective roles and build a methodology to monitor them along the life of a buyer-supplier relationship aiming at implementing new technology.
urn:nbn:de:101:1-201106143640
Keywords: M19; 650; technology partnerships; trust; relational quality; Lieferantenmanagement; Technischer Fortschritt; Innovationsmanagement; Beziehungsmarketing; Vertrauen; Kontrolle; Theorie